The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1590/fst.126522
|View full text |Cite
|
Sign up to set email alerts
|

New process of goji fermented wine: effect of goji residue degradation to generate norisoprenoid aroma compounds

Abstract: In the present study, we compared the color, flavor, and sensory attributes of wines prepared from undegraded (GW1), and physically (GW2) and biologically (GW3) degraded goji residue. Change in wine color showed a similar trend during the aging period; the color gradually became darker, with an increasing red and yellow hue. The wine obtained using the biological method was more clarified, transparent, and lustrous after 30 days of aging. Headspace solid-phase microextraction (HS-SPME) coupled to gas chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…These bioactive compounds have diverse effects, including antioxidant, antibacterial, anti-inflammatory, anti-disease, and anti-cancer properties Researchers have found that they are rich in polysaccharides, flavonoids, and phenolic acids, which can be used to produce healthy foods, functional foods, and nutritional supplements. At present, there have been reports on the production of polysaccharide phenolic acid and other food additives from jujube dregs and medlar dregs (Chen et al 2023;Farahani et al 2022). Table 6 and Fig.…”
Section: Food Additivesmentioning
confidence: 99%
“…These bioactive compounds have diverse effects, including antioxidant, antibacterial, anti-inflammatory, anti-disease, and anti-cancer properties Researchers have found that they are rich in polysaccharides, flavonoids, and phenolic acids, which can be used to produce healthy foods, functional foods, and nutritional supplements. At present, there have been reports on the production of polysaccharide phenolic acid and other food additives from jujube dregs and medlar dregs (Chen et al 2023;Farahani et al 2022). Table 6 and Fig.…”
Section: Food Additivesmentioning
confidence: 99%